Elitarne licea francuskie, dostęp do grandes ecoles i standardyzowane formowanie elit we Francji = Elitary secondary schools in France, access to grandes ecoles and the standardized formation of French elites - Gromkowska-Melosik, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
It is a common social conviction that higher education decides of an individual?s socioprofessional success. It difficult to object to this statement. However, many studies expose the fact that secondary school decides (beside the family factor) of the formation of an individual`s cultural capital, and its social "potential". It is difficult to overrate the role of elite secondary schools, either in historical context or contemporarily. The authors present the role of elite French grandes ecoles in the formation of elites in France.
Keywords: szkolnictwo ponadpodstawowe; proces kształcenia; socjalizacja; secondary school; process of education; socialization